Effect of Hydrogen Addition on Biogas Combustion and Flame Propagation (Jurnal Mekanikal, 2019)
Combustion and burning velocity of hydrogen enriched biogas-air mixture have beeninvestigated in this study from an equivalence ratio of 0.4 up to stoichiometric. Hydrogenaddition was varied from 10 to 40% based on the volume fraction. Flame buoyancy wasobserved for leaner mixture especially at an equivalence ratio of 0.4, while mild cellularitywas observed for the equivalence ratios of 0.4 and 0.5 during the later stage of the flamepropagation. Flame appears to become less stable under leaner conditions as supportedby the occurrence of buoyancy and mild cellularity at the equivalence ratios of 0.4 and 0.5under 30% and 40% of hydrogen addition. It was found that for 30% and 40% addition,the flammability limits extend to the leaner side. The maximum burning velocity occurs atan equivalence ratio of 0.8 for all mixtures regardless of the hydrogen enrichmentpercentage. The flame speed was enhanced with hydrogen enrichment at higher than 30%which led to a significant increase in the burning velocity These observations show that theaddition of hydrogen into biogas combustion will lead to an increase in the flamepropagation and burning velocity.
Keywords: Biogas; hydrogen addition; burning velocity; cellularity